A Study of Reading and Spelling Skills with Cooperative Learning Management by using CIRC Technique Integrated with Multimedia for Prathom Suksa 1 Students - Phunongong, Pimsiri; Anutragulchai, Ratchaniwan (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were 1) to study reading and spelling skills with cooperative learning management by using CIRC technique integrated with multimedia for Prathom Suksa 1 students to have average score of more than 70% and more than 70% of students passed the criteria, 2) to study the satisfaction of students towards learning with cooperative learning management by using CIRC technique integrated with multimedia. The target group consisted of 25 Prathom Suksa 1 students in Pak Khat Kindergarten school under the Office of Bueng Kan Educational Service Area, in academic year of 2019. This research was pre-experimental, one-group post-test research design. The instruments used in the research were : 1) 11 Reading and Spelling lesson Plans. 2) Reading and spelling skill test, multiple choice type with 3 choices of 20 items. 3) The student satisfaction test with total number of 15 items. The statistics used to analyze data comprised percentage, mean and standard deviation. The research results showed that: 1. Students’ reading and spelling skills were rated at average score of 18.16 out of 20 marks or 90.80% and 23 students were qualified or 92.00% of the total number of students which it was rated at the set criteria. 2. Students' satisfaction towards cooperative learning management by using CIRC technique integrated with multimedia was rated at the highest level with average score of 4.60 and standard deviation of 0.57.